2013
DOI: 10.1002/bbb.1455
|View full text |Cite
|
Sign up to set email alerts
|

New perspective for biorefining cereals

Abstract: We present a novel approach for the valorization of cereals as major renewable resources for food, functional molecules, and materials as well as for bioenergy. We use a dual approach matching numerous production options (technology push) with the wide range of requested and needed end‐products in a bio‐based society (market pull or reversed engineering). The approach is based on the enlarged concept of biorefining, taking into account global and local requirements and trends. Hence, on one hand, it focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…As indicated by Schutyser and van der Goot (2011) and Abecassis et al (2014) better understanding of the limiting Fig. 3.…”
Section: Further Research On Legume Morphology and Dry Fractionationmentioning
confidence: 72%
See 1 more Smart Citation
“…As indicated by Schutyser and van der Goot (2011) and Abecassis et al (2014) better understanding of the limiting Fig. 3.…”
Section: Further Research On Legume Morphology and Dry Fractionationmentioning
confidence: 72%
“…For example, on the one hand higher amounts of oil are less desired in relation to foaming behaviour, but on the other hand presence of more water binding fibres improves gelling behaviour of the protein fractions. Overall, it can be concluded that dry fractionation is promising for the novel design of processes were the full legume is used in a more integrated and efficient way, while attention should be paid to the increased variability in composition of the fractions (Abecassis, de Vries, & Rouau, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Certain regions in Europe may rapidly lose competitiveness due to higher production costs compared to other cereals (common wheat). Finally, renewed focus on value recovery from co-products of entire cereal plants, like the lignocellulosic part or hulls of the grains, for biomaterials and functional molecules and, in part, bio-energy fits with in the latest bio-economy concepts that focus on cascading the use of plant constituents (Abecassis et al, 2014).…”
Section: Evolution Of New Environmental Regulationsmentioning
confidence: 99%
“…In order to further increase the competitiveness of small-scale processing of durum wheat products, early new biorefinery concepts have been proposed, tested and described in detail in a recent review article (Abecassis et al, 2014). This basics here are cascading processes to valorize all durum wheat plant parts, including lignocellulose, according to volumes and value (from large volumes and low prices at the bottom to low volumes at high values at the top).…”
Section: Processing and Biorefining Durum Wheat Cereals At Small Scalmentioning
confidence: 99%